Application study of curcumin fluorescent complex coated with pharmaceutical excipients for cell imaging - Shao, Chen; Zhang, Xiaoli; Shao, Shihe; Jin, Feng (Frontiers in Chemistry, 2023)
Taking curcumin as the starting point, β-cyclodextrin was introduced on both sides, and lipid-soluble curcumin was coated by acrylic resin using oil-in-water strategy. Four different types of curcumin fluorescent complexes EPO-Curcumin (EPO-Cur), L100-55-Curcumin (L100-55-Cur), EPO -Curcumin-β-cyclodextrin (EPO-Cur-β-cd) and L100-55-Curcumin-β-cyclodextrin (L100-55-Cur-β-cd) were prepared to solve their own solubility and biocompatibility issues. The prepared curcumin fluorescent complexes were characterized and tested by spectroscopy. The characteristic peaks of 3446cm-1(hydroxyl group), 1735cm-1(carbonyl group) and 1455cm-1(aromatic group) were determined in the infrared spectrum. In the fluorescence emission spectrum, it was found that the emission intensity of different curcumin fluorescent complexes in polar solvents reached hundreds of times. Through the transmission electron microscopy shows that acrylic resin tightly coats curcumin into rods or clusters. In order to observe their compatibility with tumor cells more directly, live cell fluorescence imaging was carried out, and it was found that all four kinds of curcumin fluorescence complexes had good biocompatibility. In particular, the effect of EPO-Cur-β-cd and L100-55-Cur-β-cd is better than that of EPO-Cur and L100-55-Cur.